2023
DOI: 10.3390/plants12010220
|View full text |Cite
|
Sign up to set email alerts
|

Mapping QTL for Phenological and Grain-Related Traits in a Mapping Population Derived from High-Zinc-Biofortified Wheat

Abstract: Genomic regions governing days to heading (DH), days to maturity (DM), plant height (PH), thousand-kernel weight (TKW), and test weight (TW) were investigated in a set of 190 RILs derived from a cross between a widely cultivated wheat-variety, Kachu (DPW-621-50), and a high-zinc variety, Zinc-Shakti. The RIL population was genotyped using 909 DArTseq markers and phenotyped in three environments. The constructed genetic map had a total genetic length of 4665 cM, with an average marker density of 5.13 cM. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
2
5
0
Order By: Relevance
“…The pattern of subgenome-wise marker distribution is also similar, as maximum markers were located on subgenome B, and an approximately similar number of markers were mapped on A and D subgenomes. In earlier studies also, a similar pattern of QTL and marker distribution among the subgenomes for grain-quality traits was reported [ 21 , 26 ]. Krishnappa et al [ 22 ] studied a RIL population wherein none of the QTL was identified on the D subgenome due to a very less distribution of markers; however, the enrichment of the D genome with additional SNP markers in the same mapping population has significantly increased the power of QTL identification.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The pattern of subgenome-wise marker distribution is also similar, as maximum markers were located on subgenome B, and an approximately similar number of markers were mapped on A and D subgenomes. In earlier studies also, a similar pattern of QTL and marker distribution among the subgenomes for grain-quality traits was reported [ 21 , 26 ]. Krishnappa et al [ 22 ] studied a RIL population wherein none of the QTL was identified on the D subgenome due to a very less distribution of markers; however, the enrichment of the D genome with additional SNP markers in the same mapping population has significantly increased the power of QTL identification.…”
Section: Discussionsupporting
confidence: 80%
“…The conventional approach of QTL mapping depends on the genetic composition of bi-parental populations. A large number of QTLs have been identified in the last decade in wheat for the expression of GPC [ 21 , 22 , 23 , 24 , 25 ], TKW [ 26 , 27 , 28 , 29 ], and NDVI [ 30 , 31 , 32 ] through bi-parental-based conventional QTL mapping approach. However, the mapping resolution is very low in bi-parental population-based QTLs due to limited crossovers.…”
Section: Introductionmentioning
confidence: 99%
“…The observed moderate to high values of broad-sense heritability and the consistency of trait records evidenced by the significant correlations between the crop seasons suggest that a considerable part of the variation is due to inherent genetic differences among the accessions. These results agree with similar findings in bread and durum wheat for GPC [ 19 , 25 , 27 , 40 ], and TKW [ 13 , 41 ]. Given that the panel contains historical and contemporary varieties released or collected between 1925 and 2010, it is possible that the recorded genetic variance—especially for TKW—is inflated.…”
Section: Discussionsupporting
confidence: 92%
“…Lines 15, 38 and 2 have had the most averages of production index. In addition to these three lines, lines 43,8,49,16,34,50,11,20,10,57,59 and 39 had more production averages as compared to the parent Shotordandan. Regarding stress tolerance index (STI), lines 15, 38, 2 and 8 were of the most amount.…”
Section: Drought Tolerance Indicesmentioning
confidence: 99%